Learning Model of Discovery to Improve The Student’s Creativity in Class XI - Serevina, Vina; Maulana, Diki; Rizky Hasibuan, Hilma Suhailah; Riana, Evita (Universitas Negeri Surabaya, 2025)
This Classroom Action Research employs the Learning Model of Discovery to enhance students' creativity in understanding Elasticity and Hooke's Law. The research follows a classroom action research methodology. The findings reveal a progressive improvement in students' creativity across the first cycle, and second cycle. In the first cycle, non-creative students reduced to 2.8%, moderately creative students were 57.2%, creative students were 14.3%, and very creative students were 25.7%. In cycle II, non-creative students remained at 2.8%, moderately student’s creativity improved to 74.2%, creative students were 20%, and very creative students were 2.8%. Additionally, this study showed an improvement in student’s creativity, with a 0.54 N-gain, categorizing it as Average.